Peripheral Giant Cell Reparative Granuloma in the Anterior Mandible- A Case Report with Review of Literature - Bhambal, Annette M; Deshmukh, Priyanka; Trivedi, Akhil (Journal of Orofacial Research, 2022)
Peripheral giant cell granuloma is a tumor like growth in the oral cavity. It is often called as peripheral giant cell reparative granuloma. This lesion probably does not represent a true neoplasm, but rather, a reactive lesion, believed to be stimulated by local irritation or trauma. The cause, however, is not certainly known. It is believed to be arising from periodontal ligament (PDL) membrane or periosteum. This article reports a case of peripheral giant cell granuloma involving the mandibular anterior region in a 18-year-old young female patient. The lesion was completely excised at the level of periosteum and curettage was done. Follow up period of 6 months reported no recurrence.